Graphene / polyaniline composite coating and preparation method thereof
By constructing a three-dimensional conductive network and regulating surface energy, the graphene/polyaniline composite coating solves the problem of hydrophobicity loss and corrosion caused by corona discharge in RTV coatings in high-voltage transmission lines, achieving the integrated effect of electric field equalization and corrosion protection.
Patent Information
- Application Number
- CN202510863437.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-25
- Publication Date
- 2025-10-17
AI Technical Summary
In high-voltage transmission lines, RTV coatings lose their hydrophobicity due to corona discharge, forming a vicious cycle that makes it impossible to effectively suppress corona discharge and prevent corrosion. Traditional coating solutions have problems such as poor interface compatibility, insufficient corona protection, and functional fragmentation.
A graphene/polyaniline composite coating is used to construct a three-dimensional continuous conductive network. The passivation effect of polyaniline and the dense barrier effect of graphene are utilized to synergistically block the penetration of corrosive media. The surface energy is regulated by a fluorinated modifier to achieve self-maintenance of hydrophobicity and electric field homogenization.
It effectively suppresses corona discharge, maintains stable hydrophobicity of the coating, reduces corrosion risk, improves the coating's conductive current-sharing capability and anti-corrosion effect, and solves the problem of coupling between corona discharge and corrosion.
Smart Images

Figure SMS_1
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of power transmission line coating, and particularly relates to a graphene / polyaniline composite coating and a preparation method thereof. BACKGROUND
[0002] In high-voltage transmission lines, room temperature vulcanized silicone rubber (RTV) coating is widely used for anti-pollution flashover of insulators due to its excellent hydrophobicity and weather resistance. However, alternating current corona discharge can cause irreversible chemical structure damage on the surface of the RTV coating, significantly reducing its hydrophobicity and self-recovery ability. Ozone (O3) and high-energy electrons generated by corona discharge can oxidize the Si-CH3 group in the RTV molecular chain to form a hydrophilic Si-OH group, resulting in a decrease in the static contact angle from the initial 105° to 45° (after 4 hours of corona treatment); the hydrophobicity recovery depends on the migration of low molecular weight siloxane to the surface, but under the continuous action of corona, the surface oxidation layer hinders the migration process, and the contact angle only rises to 78° after 24 hours of natural recovery, which cannot reach the initial level.
[0003] This characteristic poses a severe challenge to the corrosion prevention of power transmission lines: the loss of hydrophobicity makes it easier for water and pollutants (such as salt mist and industrial dust) to adhere, forming an electrolyte film and accelerating the electrochemical corrosion of metal components (such as wires and fittings); traditional RTV coating lacks the ability to conduct current and equalize current, and cannot inhibit the continuous occurrence of corona discharge, forming a vicious cycle of "corona damage-hydrophobicity decrease-corrosion aggravation".
[0004] In the prior art, in order to solve the problem of coupling of corona and corrosion, a step-by-step coating scheme of conductive coating + corrosion-resistant coating (such as galvanized layer + epoxy resin) is usually used. However, this scheme has the following defects:
[0005] Poor interface compatibility: the thermal expansion coefficients of the conductive layer and the corrosion-resistant layer do not match, and microcracks are easily generated under temperature stress (experiments show that the adhesion decreases by 60% after 100 cycles at -40℃ to 80℃).
[0006] Insufficient corona protection: the surface roughness of the galvanized layer is high (Ra>5μm), which aggravates the distortion of the electric field and increases the local corona current density (simulation shows that the surface field strength of the galvanized wire is 15% to 20% higher than that of the smooth surface);
[0007] Functional fragmentation: the insulating properties of the corrosion-resistant layer (such as epoxy resin) hinder the uniform distribution of current, resulting in abnormal potential gradient and inducing local corrosion.
[0008] Therefore, it is urgent to develop an integrated coating that has the functions of conducting current and equalizing current and long-term corrosion resistance, which can inhibit corona discharge and maintain the stability of hydrophobicity by optimizing the surface physicochemical properties. SUMMARY
[0009] The application provides a graphene / polyaniline composite coating and a preparation method thereof, so as to improve the conductivity and corrosion resistance of the coating of a high-voltage transmission line.
[0010] In a first aspect, the application provides a graphene / polyaniline composite coating, comprising: an epoxy-modified silicone resin, functionalized graphene, polyaniline nanofiber, nano-oxide, silane coupling agent, and fluorinated modifier.
[0011] Optionally, the composite coating comprises a dense base layer of an inner layer and a high-conductivity surface layer of an outer layer on the transmission conductor, and the graphene content of the high-conductivity surface layer is greater than that of the dense base layer.
[0012] Optionally, the thickness of the dense base layer is 30-80 μm, and / or the thickness of the high-conductivity surface layer is 30-120 μm.
[0013] Optionally, the functionalized graphene is selected from one or more of carboxylated graphene, hydroxylated graphene, and aminated graphene.
[0014] Optionally, the polyaniline nanofiber is selected from one or more of sulfuric acid, phosphoric acid, hydrochloric acid, tannic acid, and sodium dodecyl benzene sulfonate doped polyaniline fiber.
[0015] Optionally, the nano-oxide is selected from one or more of nano-TiO2, nano-SiO2, and nano-ZnO.
[0016] Optionally, the fluorinated modifier is one or more of perfluorooctyltriethoxysilane, tridecafluorooctyltriethoxysilane, and triethylsilyl methanesulfonate.
[0017] Optionally, the silane coupling agent is selected from one or more of an amino silane coupling agent, an epoxy silane coupling agent, and a fluorosilane coupling agent.
[0018] Optionally, the epoxy-modified silicone resin accounts for 70%-85% of the mass, the functionalized graphene accounts for 1%-3% of the mass, the polyaniline nanofiber accounts for 5%-10% of the mass, the nano-oxide accounts for 2%-3% of the mass, the silane coupling agent accounts for 0.5%-1% of the mass, and the fluorinated modifier accounts for 1%-2% of the mass.
[0019] In a second aspect, the application provides a preparation method of a graphene / polyaniline composite coating, and the preparation method is used for preparing the graphene / polyaniline composite coating according to any one of the first aspect.
[0020] The transmission conductor is subjected to sand blasting treatment, and is sequentially cleaned with acetone and ethanol by ultrasonic cleaning and dried by nitrogen blowing;
[0021] Mixing graphene and polyaniline nanofiber at a mass ratio of 1:1-1:3, adding silane coupling agent, and ultrasonic dispersion in ethanol;
[0022] Adding epoxy modified silicone resin, nano-oxide and fluorinated modifier, ball milling treatment, to obtain a uniform slurry;
[0023] The slurry with a graphene content of 0.5-1.5% is electrostatically sprayed under the conditions of a substrate temperature of 80℃, a magnetic field strength of 0.2T, and a magnetic field direction parallel to the surface direction of the base material, to form a dense bottom layer;
[0024] The slurry with a graphene content of 2-5% is electrostatically sprayed under the conditions of a substrate temperature of 100℃, a magnetic field strength of 0.5T, and a magnetic field direction parallel to the surface direction of the base material, to form a high-conductivity surface layer.
[0025] Stepwise temperature curing treatment is performed to form a crosslinked network.
[0026] The graphene / polyaniline composite coating and the preparation method thereof provided by the present application include: epoxy modified silicone resin, functionalized graphene, polyaniline nanofiber, nano-oxide, silane coupling agent, and fluorinated modifier. The polyaniline passivation and the physical barrier of graphene are used to synergistically block the penetration of corrosion medium, the fluorinated modifier is used to regulate the surface energy, the water adhesion is reduced, and the problem of loss of hydrophobicity caused by corona is delayed; the functionalized graphene has good conductivity, and a three-dimensional continuous conductive network is formed in the coating, which can effectively homogenize the electric field distribution. The functions of electric field homogenization, dynamic corrosion prevention, and self-maintenance of hydrophobicity are realized, and the problem of coupling of corona discharge and corrosion of the power transmission line is solved. DETAILED DESCRIPTION
[0027] To make the objectives, technical solutions, and advantages of the present application clearer, the technical solutions in the embodiments of the present application will be described below in a clear and complete manner in combination with the embodiments of the present application. Obviously, the described embodiments are some embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those of ordinary skill in the art without creative labor fall within the protection scope of the present application.
[0028] The traditional high-voltage power transmission line coating is easy to lose its effective hydrophobicity under the action of corona discharge, and thus the corrosion problem of the metal part is aggravated.
[0029] Therefore, the present application provides a graphene / polyaniline composite coating, which can effectively homogenize the surface electric field by constructing a three-dimensional continuous conductive network, and reduce the damage of corona to the coating structure; at the same time, the passivation of polyaniline and the dense barrier effect of graphene are synergistic, which blocks the penetration of corrosion medium, and provides a solution to the failure problem of the RTV coating in the corona-corrosion coupling scenario.
[0030] The graphene / polyaniline composite coating comprises: epoxy-modified silicone resin, functionalized graphene, polyaniline nanofiber, nano-oxide, silane coupling agent and fluorinated modifier.
[0031] Epoxy-modified silicone resin provides adhesion and temperature resistance.
[0032] The functionalized graphene is one or more of carboxylated graphene, hydroxylated graphene and aminolated graphene, which constructs a three-dimensional conductive network in the system to reduce resistance.
[0033] The polyaniline nanofiber is one or more polyaniline fibers doped with sulfuric acid, phosphoric acid, hydrochloric acid, tannic acid, and sodium hexadecylbenzenesulfonate, which can passivate the metal matrix and enhance interface bonding.
[0034] The nano-oxide is one or more of nano-TiO2, nano-SiO2 and nano-ZnO, and is resistant to ultraviolet aging.
[0035] The silane coupling agent is one or more of an aminosilane coupling agent, an epoxysilane coupling agent and a fluorosilane coupling agent, and improves the dispersibility of the filler.
[0036] The fluorinated modifier is one or more of perfluorooctyltriethoxysilane, tridecafluorooctyltriethoxysilane, and triethylsilyl methanesulfonate, which reduces surface energy and improves hydrophobicity.
[0037] In some embodiments, the mass ratio of each component is: epoxy-modified silicone resin 70%~85%, functionalized graphene 1%~3%, polyaniline nanofiber 5%~10%, nano-oxide 2%~3%, silane coupling agent 0.5%~1%, and fluorinated modifier 1%~2%.
[0038] The coating system achieves an integrated solution to the anti-corona and anti-corrosion problems through the following functions and principles.
[0039] Dynamic corrosion protection: Polyaniline, a conductive polymer, has excellent metal surface passivation properties. Within the coating, the passivation effect of polyaniline, through interfacial reactions with the metal substrate, reduces contact between corrosive media (such as moisture and salt spray) and the metal substrate, thereby inhibiting the occurrence of corrosion reactions. Graphene, with its strong mechanical strength and excellent chemical stability, can form a dense barrier layer on the coating surface, preventing corrosive media from penetrating the underlying coating layer, further reducing the risk of corrosion. Graphene also exhibits excellent water-repellent properties, effectively isolating external water and gases, thereby preventing corrosion reactions.
[0040] Self-sustaining hydrophobicity: By surface energy regulation, reduce water adhesion, delay the problem of hydrophobicity loss of RTV type coating caused by corona. Fluorinated modifiers (such as perfluorooctyltriethoxysilane) can significantly reduce the surface energy of the coating, improve the hydrophobicity of the coating, and reduce the adhesion of water. By reducing the residence time of water droplets on the surface of the coating, these modifiers help to maintain the hydrophobicity of the coating and prevent the loss of hydrophobicity of the coating caused by corona discharge. The two-dimensional structure of graphene can effectively reduce the surface energy of the coating, further enhancing its waterproof ability. The conductivity and hydrophilic properties of polyaniline can adjust the surface properties of the coating to some extent, so that it can still maintain a certain self-recovery ability under the action of corona, avoiding the complete loss of hydrophobicity under the action of corona for a long time.
[0041] Electric field homogenization: Functionalized graphene (such as carboxylated, hydroxylated or aminated graphene) has good conductivity, which can effectively homogenize the electric field distribution by forming a three-dimensional continuous conductive network in the coating. The role of electric field homogenization is to reduce the local enhancement of electric field and reduce the intensity of corona discharge, avoiding the damage of corona discharge to the structure of the coating. The conductive network of graphene not only reduces the concentration of current, but also effectively reduces the damage of corona discharge to the coating, thereby enhancing the stability of the coating.
[0042] In some embodiments, the composite coating on the power transmission wire includes a dense base layer of the inner layer and a high-conductive surface layer of the outer layer, and the graphene content in the dense base layer and the high-conductive surface layer is different. The graphene content of the high-conductive surface layer is greater than that of the dense base layer.
[0043] The dense base layer has a low graphene content (0.5-1.5%), which mainly serves as the base of the coating, providing strong adhesion and good barrier performance to prevent the penetration of corrosive media. The dense structure of the base layer can effectively block the external environment from damaging the coating substrate, while improving the wear resistance and corrosion resistance of the coating.
[0044] The high-conductive surface layer has a high graphene content (2-5%), which has better conductivity and can homogenize the electric field distribution, reducing the damage of corona effect to the coating. The high conductivity of the surface layer also improves the anti-electric field interference ability of the coating, making the coating more stable in power transmission.
[0045] The two-layer structure can effectively improve the electrical performance of the coating. The dense base layer can reduce the resistance of the coating and form a more stable electric field shielding effect. The high-conductive surface layer of the outer layer enhances the conduction ability of the coating to the current, avoiding the excessive concentration of electric field and reducing the risk of corona discharge. This layered design can optimize the electrical performance of the entire coating system.
[0046] In some embodiments, the thickness of the dense bottom layer is 30-80 μm. For example, the thickness can be 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, or a range consisting of any two of the above values.
[0047] In some embodiments, the thickness of the highly conductive surface layer is 30-120 μm. For example, the thickness may be 30 μm, 50 μm, 70 μm, 90 μm, 110 μm, 130 μm, or a range consisting of any two of the above values.
[0048] The present application also provides a method for preparing a graphene / polyaniline composite coating, the preparation method comprising:
[0049] Step 1: Substrate Pretreatment
[0050] The transmission wires were sandblasted (Sa 2.5), then ultrasonically cleaned with acetone and ethanol, and dried with nitrogen.
[0051] Step 2: Preparation of graphene / polyaniline composite slurry
[0052] Graphene and polyaniline nanofibers were mixed in a mass ratio of 1:1-1:3, a silane coupling agent was added, and ultrasonic dispersion was performed in ethanol for 30 minutes (power 300W);
[0053] Epoxy-modified silicone resin, nano-oxide and fluorinated modifier were added, and ball milling was performed for 2 hours (rotation speed 400 rpm, zirconia ball diameter 1 mm) to obtain a uniform slurry.
[0054] Step 3: Gradient coating spray
[0055] Using electrostatic spraying + magnetic field orientation process:
[0056] Bottom layer spraying: The graphene content in the slurry is 0.5-1.5%, the spraying voltage is -50kV, the substrate temperature is 80℃, the magnetic field intensity is 0.2T (direction parallel to the substrate surface), and a dense bottom layer (thickness 30-80μm) is formed;
[0057] Surface spraying: The graphene content in the slurry is 2-5%, the spraying voltage is -60kV, the substrate temperature is 100℃, and the magnetic field strength is 0.5T, so that the graphene sheets are horizontally oriented to form a highly conductive surface layer (thickness 30-120μm).
[0058] Step 4: Curing
[0059] Step-by-step curing: pre-curing at 80°C for 1 hour, curing at 120°C for 2 hours, and post-curing at 150°C for 1 hour to form a cross-linked network.
[0060] Specific embodiments and test data
[0061] Example 1
[0062] The graphene / polyaniline composite coating is composed of the following components (mass percentage): epoxy-modified silicone resin 75%, carboxylated graphene (flaky diameter 8 μm) 3%, sulfuric acid-doped polyaniline nanofiber 6%, nano-TiO2 2.5%, KH-560 silane coupling agent 1%, perfluorooctyl triethoxysilane 2.5%.
[0063] The graphene / polyaniline composite coating is prepared according to the following steps:
[0064] 1. Substrate pretreatment: sandblasting treatment (Sa 2.5 level) is performed on the power transmission wire (aluminum alloy), followed by ultrasonic cleaning with acetone and ethanol in sequence, and nitrogen blowing for drying;
[0065] 2. Preparation of slurry: graphene and polyaniline are mixed at a ratio of 1:2, and the addition amount of KH-560 is 1%, ultrasonic dispersion for 30 minutes (300 W);
[0066] 3. Gradient spraying:
[0067] Bottom layer: graphene content 1.5%, spraying voltage -50 kV, magnetic field 0.2 T, thickness 50 μm;
[0068] Top layer: graphene content 5%, spraying voltage -60 kV, magnetic field 0.5 T, thickness 30 μm;
[0069] 4. Curing: 80°C / 1 h, 120°C / 2 h, 150°C / 1 h.
[0070] Example 2
[0071] The graphene / polyaniline composite coating is composed of the following components (mass percentage): epoxy-modified silicone resin 80%, aminated graphene (flaky diameter 5 μm) 2%, phosphoric acid-doped polyaniline nanofiber 5%, nano-SiO2 (particle size 20 nm) 3%, KH-550 silane coupling agent 0.8%, tridecafluoro-octyl triethoxysilane 2.2%.
[0072] The graphene / polyaniline composite coating is prepared according to the following steps:
[0073] 1. Substrate pretreatment: same as Example 1;
[0074] 2. Preparation of slurry: graphene and polyaniline are mixed at a ratio of 1:1, and the addition amount of KH-550 is 0.8%, ball milling dispersion;
[0075] 3. Gradient spraying:
[0076] Bottom layer: graphene content 0.5%, magnetic field 0.2 T, thickness 80 μm;
[0077] Top coat: graphene content 4%, magnetic field 0.5 T, thickness 50 pm;
[0078] 4. Curing: same as Example 1.
[0079] Example 3
[0080] The graphene / polyaniline composite coating was composed of the following parts (mass percentage) epoxy modified silicone resin 70%, hydroxylated graphene (flake diameter 10 pm) 1.5%, tannic acid doped polyaniline nanofiber 8%, nano-ZnO (particle size 30 nm) 2.5%, KH-570 silane coupling agent 0.5%, triethylsilyl methanesulfonate 3%.
[0081] The graphene / polyaniline composite coating was prepared according to the following steps:
[0082] 1. Substrate pretreatment: same as Example 1.
[0083] 2. Preparation of slurry: graphene and polyaniline were mixed at a ratio of 1:3, and the addition amount of KH-570 was 0.5%.
[0084] 3. Gradient spraying:
[0085] Bottom coat: graphene content 1%, magnetic field 0.2 T, thickness 30 pm;
[0086] Top coat: graphene content 2.5%, magnetic field 0.5 T, thickness 120 pm;
[0087] 4. Curing: same as Example 1.
[0088] Comparative Example 1: traditional RTV coating
[0089] Under the same conditions of corona aging and recovery as in the example, the contact angle decreased from 105° to 52°, and after recovery, only 82°;
[0090] Surface resistivity > 10 14 Ω·cm, unable to achieve current sharing effect.
[0091] Comparative Example 2: graphene / epoxy coating
[0092] Salt spray resistance 1800 hours pitting occurred.
[0093] No hydrophobic recovery function, contact angle continuously decreased after corona aging.
[0094] The data of the test results are shown in Table 1.
[0095]
[0096] The graphene / polyaniline composite coating structure has sparse graphene in the bottom layer and dense graphene in the surface layer, achieving the structure of "mainly surface conduction and auxiliary interlayer corrosion inhibition"; the -NH2 of polyaniline and the -COOH of graphene form amide bonds (FTIR confirms the characteristic peak at 1640 cm -1 ) during the curing process, reducing the interface contact resistance (≤10 -3 Ω·cm 2 ); when the coating is damaged, the oxidation state of polyaniline promotes the generation of a passivation film on the exposed metal surface (XPS shows that the content of Al2O3 increases by 20%).
[0097] Finally, it should be noted that: the above embodiments are only used to illustrate the technical solutions of the present application, and not to limit them; although the present application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that: it can still modify the technical solutions recorded in the foregoing embodiments, or make equivalent replacement for part or all of the technical features; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A graphene / polyaniline composite coating, characterized in that: include: Epoxy modified silicone resin, functionalized graphene, polyaniline nanofiber, nano oxide, silane coupling agent, fluorinated modifier.
2. The composite coating according to claim 1, characterized in that The composite coating comprises an inner dense bottom layer and an outer high-conductivity surface layer on the transmission wire, and the graphene content of the high-conductivity surface layer is greater than the graphene content of the dense bottom layer.
3. The composite coating according to claim 2, characterized in that The thickness of the dense bottom layer is 30-80 μm, and / or the thickness of the high conductive surface layer is 30-120 μm.
4. The composite coating according to any one of claims 1 to 3, characterized in that: The functionalized graphene is selected from one or more of carboxylated graphene, hydroxylated graphene and aminolated graphene.
5. The composite coating according to any one of claims 1 to 3, characterized in that: The polyaniline nanofibers are selected from one or more polyaniline fibers doped with sulfuric acid, phosphoric acid, hydrochloric acid, tannic acid, and sodium hexadecylbenzenesulfonate.
6. The composite coating according to any one of claims 1 to 3, characterized in that: The nano-oxide is selected from one or more of nano-TiO2, nano-SiO2 and nano-ZnO.
7. The composite coating according to any one of claims 1 to 3, characterized in that: The fluorinated modifier is one or more of perfluorooctyltriethoxysilane, tridecafluorooctyltriethoxysilane, and triethylsilyl methanesulfonate.
8. The composite coating according to any one of claims 1 to 3, characterized in that: The silane coupling agent is selected from one or more of an aminosilane coupling agent, an epoxysilane coupling agent and a fluorosilane coupling agent.
9. The composite coating according to any one of claims 1 to 3, characterized in that: The mass of epoxy-modified silicone resin accounts for 70%~85%, the mass of functionalized graphene accounts for 1%~3%, the mass of polyaniline nanofibers accounts for 5%~10%, the mass of nano-oxides accounts for 2%~3%, the mass of silane coupling agents accounts for 0.5%~1%, and the mass of fluorinated modifiers accounts for 1%~2%.
10. A method for preparing a graphene / polyaniline composite coating, characterized in that: The preparation method is used to prepare the graphene / polyaniline composite coating according to any one of claims 1 to 9, and the preparation method comprises: The transmission wires were sandblasted, ultrasonically cleaned with acetone and ethanol, and dried with nitrogen; Graphene and polyaniline nanofibers were mixed in a mass ratio of 1:1-1:3, a silane coupling agent was added, and ultrasonic dispersion was performed in ethanol; Add epoxy modified silicone resin, nano oxide and fluorinated modifier, and ball mill to obtain uniform slurry; Electrostatically spray a slurry with a graphene content of 0.5-1.5% at a substrate temperature of 80°C, a magnetic field strength of 0.2T, and a magnetic field direction parallel to the substrate surface to form a dense bottom layer; Electrostatically spray a slurry with a graphene content of 2-5% at a substrate temperature of 100°C, a magnetic field strength of 0.5T, and a magnetic field direction parallel to the substrate surface to form a highly conductive surface layer; Step-by-step temperature curing treatment forms a cross-linked network.